Perspectives of pregnant and breastfeeding women on longitudinal clinical studies that require non-invasive biospecimen collection – a qualitative study - Lemas, Dominick J.; Wright, Lauren; Flood-Grady, Elizabeth; Francois, Magda; Chen, Lynn; Hentschel, Austen; Du, Xinsong; Hsiao, Chu J.; Chen, Huan; Neu, Josef; Theis, Ryan P.; Shenkman, Elizabeth; et al. (BMC pregnancy and childbirth, 2021)
Investigation of the microbiome during early life has stimulated an increasing number of cohort studies in pregnant and breastfeeding women that require non-invasive biospecimen collection. The objective of this study was to explore pregnant and breastfeeding women's perspectives on longitudinal clinical studies that require non-invasive biospecimen collection and how they relate to study logistics and research participation. We completed in-depth semi-structured interviews with 40 women who were either pregnant (n = 20) or breastfeeding (n = 20) to identify their understanding of longitudinal clinical research, the motivations and barriers to their participation in such research, and their preferences for providing non-invasive biospecimen samples. Perspectives on research participation were focused on breastfeeding and perinatal education. Participants cited direct benefits of research participation that included flexible childcare, lactation support, and incentives and compensation. Healthcare providers, physician offices, and social media were cited as credible sources and channels for recruitment. Participants viewed lengthy study visits and child protection as the primary barriers to research participation. The barriers to biospecimen collection were centered on stool sampling, inadequate instructions, and drop-off convenience. Women in this study were interested in participating in clinical studies that require non-invasive biospecimen collection, and motivations to participate center on breastfeeding and the potential to make a scientific contribution that helps others. Effectively recruiting pregnant or breastfeeding participants for longitudinal microbiome studies requires protocols that account for participant interests and consideration for their time.